ANALISIS BUKU AJAR BAHASA ARAB MADRASAH IBTIDAIYAH KELAS II TERBITAN KEMENAG RI TAHUN 2020 - Dwi Aulia Putri (Jurnal Sathar, 2026)
This study critically analyzes the Grade II Arabic textbook published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020 to determine its conformity with national textbook standards and the principles of effective Arabic language instruction. Using a qualitative library-research approach and content analysis, the study examines the book’s structure, linguistic accuracy, and pedagogical alignment. The findings reveal significant issues in the selection, sequencing, and integration of materials; inconsistencies in linguistic accuracy and transliteration; as well as weak connections between vocabulary, grammar, and exercises. The graphic elements and illustrations were also found to be inconsistent, pedagogically unsupportive, and sometimes confusing for young learners. Although the textbook meets moral and national value requirements, it does not fully comply with BSNP standards regarding content, presentation, language, and graphics. Therefore, a comprehensive revision is necessary to make the textbook more effective and appropriate for Madrasah Ibtidaiyah students.